EFFECTS OF ETHICAL LEADERSHIP ON EMPLOYEE WELL-BEING: THE MEDIATING ROLE OF PSYCHOLOGICAL EMPOWERMENT - Shania Dwi Rantika; andi ina yustina (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Leaders who promote ethical behavior are believed to affect their employees’ well-being. This study was conducted to examine psychological empowerment as the intervening variable that connects ethical leadership to employees’ well-being, work engagement, and emotional exhaustion. By using a mail survey, we distributed questionnaires to 219 auditors from 11 public accounting firms in Jakarta. All the hypotheses in this study were supported. Ethical leadership has a positive effect on psychological empowerment. Thus, psychological empowerment positively relates to work engagement and negatively relates to emotional exhaustion. The result demonstrated that psychological empowerment partially mediates the effect of ethical leadership on work engagement and fully mediates the effect on ethical leadership and emotional exhaustion. The findings reveal that ethical leadership stimulates the psychological empowerment of the employee, thus, it enhances work engagement and also minimizes emotional exhaustion.